2010
DOI: 10.1097/mot.0b013e3283402beb
|View full text |Cite
|
Sign up to set email alerts
|

Mature wines are better: CDC as the leading method to define highly sensitized patients

Abstract: A proper designation of highly sensitized patients is crucial since it impacts the allocation. CDC-DSA is generally considered a contraindication for transplantation, whereas SPA-DSA remains controversial. The lack of consensus between centers is partly due to the heterogeneity of the HLA antibodies involved, the lack of standardization in antibody titer, the immunoglobulin (sub)class and the epitopes recognized. Until the issues are resolved, one should be careful to use the information generated in SPA for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
(13 reference statements)
0
10
2
1
Order By: Relevance
“…The cases presented in this article strongly suggest the use of the AMS-ELISA as alternative solid phase-based crossmatch procedure to overcome the general problem of artificially positive CDC-CM results. Hence, the results presented here are not at all in accord with attempts to declare the CDC-based procedures as leading methods and as "gold standard" as proposed a few years ago [25]. Quite contrary to this proposal the cases presented here show the general insufficiency of CDC-based assays to lead to valid results under the accompanying immune complex disease SLE.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The cases presented in this article strongly suggest the use of the AMS-ELISA as alternative solid phase-based crossmatch procedure to overcome the general problem of artificially positive CDC-CM results. Hence, the results presented here are not at all in accord with attempts to declare the CDC-based procedures as leading methods and as "gold standard" as proposed a few years ago [25]. Quite contrary to this proposal the cases presented here show the general insufficiency of CDC-based assays to lead to valid results under the accompanying immune complex disease SLE.…”
Section: Discussioncontrasting
confidence: 91%
“…From December 2010 the determining factor was not whether these new guidelines were immunologically and diagnostically worthwhile to circumvent erroneous outcomes or not since to date they have been obligatory. Both the publication of the Eurotransplant authorities Doxiadis and co-workers [25] and the corresponding amendment of the guidelines of the German Federal Medical Association from 2010 must be regarded as anachronistic as the use of novel crossmatch assays to substitute or at least to complement the standard CDC-CM has increasingly been discussed over the last 8-10 years due to this procedure's apparent drawbacks. More than 30 years ago, Ozturk and Terasaki already reported that autoantibodies and immune complexes such as rheumatoid factors may lead to false-positive results of CDC-crossmatches [26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the two cases presented here suggest the use of the AMS-ELISA to overcome the general problem of artificially positive CDC-based crossmatch results. However, the results presented are not in accordance with the latest attempts to declare the CDC-based procedures as the leading method for the definition of immunized patients as proposed recently [12]. Quite in contrast they show the general insufficiency of CDC-based assays to lead to valid results under the conditions described demonstrating the urgent need to substitute them at least for special groups of patients.…”
Section: Discussioncontrasting
confidence: 68%
“…Depending on the prognosis of the patient, the clinician should decide when it is acceptable to take this risk to proceed with transplant recognizing the presence of DSA. In case of highly sensitized patients, DSA detectable by Luminex SAB should not be considered the sole determinant of unacceptable mismatches .…”
Section: Challenging Medical Decisionsmentioning
confidence: 99%